Implementasi Pendidikan Karakter Lokal Kasundaan Berbasis Kebijakan SPBS di Kabupaten Sumedang Jawa Barat - Nurjaman, Omay Komara; Julia, Julia (Mimbar Sekolah Dasar, 2018)
This study aims to analyze the implementation of policy on kasundaan character education based on Sumedang Regent regulation about Sumedang Puseur Budaya Sunda (SPBS). The method used was a survey to the elementary school students, which was completed with interviews and FGD. The results of the study found that: (1) SPBS was only instructed in the "SKPD" environment only in the form of Thursday using kasumedangan dress and Sundanese language, (2) no education design of kasundaan characters in elementary school, (3) the majority of elementary school students already have the expected behavior in the context of kasundaan values based on Regent's regulation on SPBS. However, a few other minorities, in fact, show the unexpected behavior that potentially leads the students to negative behavior. Thus, it can be concluded that the implementation of kasundaan character education in elementary school in Sumedang conducted only based school curriculum in spite of Regent’s regulation.